ANALYSIS OF POWER EFFICIENCY OF A DIRECT-DRIVEN LOCALLY FABRICATED PERMANENT MAGNET AC GENERATOR FOR SMALL-SCALE WIND POWER APPLICATIONS IN TANZANIA - Msuya, R A; Kainkwa, R R. M; Mgwatu, M I (Tanzania Journal of Engineering and Technology, 2017)
The use of direct-driven permanent magnet alternating current (AC) generators offers the opportunity to reduced costs and increased system efficiency. This type of generator could be the best alternative for rural population whom are not connected to the national grid. To improve the design and efficiency of locally fabricated generators, it is imperative to characterize both their mechanical and electrical parameters. This paper presents the analysis of power efficiency of the synchronous permanent AC generator locally fabricated in Tanzania. In this case, load resistance and rotational speed are characterized using designed experiment. The output current and voltage of the generator were recorded simultaneously in each step change of load resistance and rotational speed. The output power and efficiency were then determined analytically. The results show that there is a linear relationship between voltage and rotational speed of the generator with and without load resistance. The results further indicated that out power is not linearly related to rotational speed. The generator €¢s power efficiency was found to be about 55% against both the output voltage and rotational speed.